Implementation of the KNN Method to Predict the Literacy Rate of Residents Aged Over 15 Years on Sulawesi Island - Jimsan, Jimsan; Iin, Johar Nur; Ayuningsih, Ekatri (Bahasa Indonesia, 2024)
AMH (Literacy Rate) is the percentage or proportion of individuals in a population who have the ability to read and write. In particular, literacy rates are often used to measure the literacy level of a region or country. Literacy rates are one of the important things for economic growth and reducing poverty rates. AMH is also a factor that influences life expectancy. This research aims to predict the percentage of AMH aged 15 years and over using the K-Near Neighbor (KNN) method specifically in the Sulawesi Island area, namely Southeast Sulawesi, South Sulawesi, West Sulawesi, North Sulawesi, Central Sulawesi and Gorontalo. This classification uses data taken from the website of the Central Statistics Agency (BPS) of the Republic of Indonesia, namely data on the AMH percentage of the population aged over 15 years in the Sulawesi Island area in 2017-2023. The working principle of K-Nearest Neighbor is to find the shortest distance between the test data and the training data. The results of this research showed the prediction of the percentage of AMH (literacy rate) of the population aged over 15 years in the Sulawesi Island area in the following year (2024). Meanwhile, test results using MAPE show that the prediction of the AMH percentage in 2024 by the KNN algorithm has quite good accuracy. The MAPE calculation results for the prediction of the AMH percentage in 2024 are 0.594307365%.